2023
DOI: 10.3389/fpsyt.2023.1264998
|View full text |Cite
|
Sign up to set email alerts
|

Substance use during pregnancy and risk of postpartum depression: a systematic review and meta-analysis

Malein Pacho,
Claudia Aymerich,
Borja Pedruzo
et al.

Abstract: IntroductionPostpartum depression (PPD) is a prevalent mental health condition affecting women globally within the first year following childbirth. Substance use during pregnancy has been associated with an increased risk of developing PPD, but the evidence remains inconclusive. This meta-analysis aims to comprehensively assess the effects of different substances on PPD risk, exploring potential modifiers and confounding factors.ObjectivesTo examine the proportion of PPD among substance users during pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Prior studies have documented co-occurrence of impaired MMH and substance use ( Pentecost et al, 2021 ). For example, a recent systematic review and meta-analysis demonstrated that the prevalence of postpartum depression (PPD) among women with prenatal substance use is markedly higher than the estimated rate of PPD among the general population (29% vs. 17%) ( Pacho et al, 2023 ). Although antenatal substance use and impaired mental health are frequently co-occurring, their respective repercussions on obstetric and neonatal outcomes are often investigated as independent risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have documented co-occurrence of impaired MMH and substance use ( Pentecost et al, 2021 ). For example, a recent systematic review and meta-analysis demonstrated that the prevalence of postpartum depression (PPD) among women with prenatal substance use is markedly higher than the estimated rate of PPD among the general population (29% vs. 17%) ( Pacho et al, 2023 ). Although antenatal substance use and impaired mental health are frequently co-occurring, their respective repercussions on obstetric and neonatal outcomes are often investigated as independent risk factors.…”
Section: Introductionmentioning
confidence: 99%